Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 5th International Conference on Physical Education, Sport, and Health (ACPES 2019) 2019
DOI: 10.2991/acpes-19.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Probiotic Supplementation on Football Player’s Stress and Anxiety

Abstract: Psychobiotics derived from probiotics which contain psychotropic properties, and with correct administration can positively affect the psychological states. Athletes who go through strenuous training are more vulnerable to undergo stress and anxiety. Thus, the objective of this study is to determine the effect of daily probiotics supplementation on stress and anxiety among the football players. The randomised, doubleblinded, placebo-controlled trial was conducted using 20 male footballers (age 19.0 ± 0.72 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…This study showed that stress and anxiety in badminton players could be alleviated with the daily consumption of probiotics for six weeks. The findings in this study were strongly supported by Adikari et al (2019), which observed a significant decrease in competitive anxiety and perceived stress among 20 football players after eight weeks of daily probiotic supplementation [ 33 ]. Moreover, the findings were also consistent with those reported by Allen et al (2016), where stress and anxiety levels of a healthy population were observed to decrease after four weeks of probiotic supplementation [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study showed that stress and anxiety in badminton players could be alleviated with the daily consumption of probiotics for six weeks. The findings in this study were strongly supported by Adikari et al (2019), which observed a significant decrease in competitive anxiety and perceived stress among 20 football players after eight weeks of daily probiotic supplementation [ 33 ]. Moreover, the findings were also consistent with those reported by Allen et al (2016), where stress and anxiety levels of a healthy population were observed to decrease after four weeks of probiotic supplementation [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…The portion sizes of the foods consumed were estimated using household measurements. A qualified nutritionist performed the diet analyze through the Nutritionist Pro TM (Axxya Systems, Woodinville, WA, USA) software version 2.4.1 (First Data Bank INC., 2011) based on the Malaysian food database as reported previously [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of positive effect was explained by the production of SCFAs and anti-inflammatory substances [27]. Another randomized, double-blinded, placebo-controlled clinical trial, where Lactobacillus casei Shirota was given to 20 male football players for 8 weeks, showed a decrease in cognitive state anxiety scores, somatic state, and perceived stress scale [28]. A randomized, placebo-controlled, double-blind clinical trial where Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 were given to 110 depressed patients (81 completed the trial) showed a significant decrease in Beck Depression Inventory (BDI) score.…”
Section: Psychobiotics In Mental Healthmentioning
confidence: 99%
“…Anxiety and perceived stress were measured at the beginning of the study, at week 4, and week 8, using the anxiety inventory as a competitive state and the scale of the level of stress experienced. Daily psychobiotic supplementation was found to significantly reduce the results of anxiety as a cognitive state, somatic state, and perceived stress levels [ 203 ]. The study did not measure biological parameters, so the mechanism of action by which the strain selected in the study eliminated anxiety behavior was not identified [ 204 ].…”
Section: The Role Of Psychobiotics In the Prevention And Treatmentmentioning
confidence: 99%